Effect of bioaugmentation on biochemical characterisation and microbial communities in Daqu using Bacillus, Saccharomycopsis and Absidia. (8th April 2019) - Song, Jiankun; Tang, Hanlan; Liang, Hebin; Luo, Lixin; Lin, Weifeng
Summary: Daqu, a saccharifying and fermenting agent for the production of Chinese vinegar and liquor, is manufactured through a spontaneous solid‐state fermentation process (SSF). To investigate the influence of bioaugmentation with native microorganisms on Daqu SSF process, physicochemical properties, microbial biomass, volatile compounds and microbial communities were analysed in laboratory‐scale Daqu . The results showed that the amylase activity of Daqu enhanced 6.35% ± 0.74% by inoculating Bacillus amyloliquefaciens, Saccharomycopsis fibuligera and Absidia corymbifera . Obviously higher microbial richness was found in the Daqu with bioaugmentation, although the microbial community structure remained relatively stable. Moreover, a total of twenty‐two volatile compounds were detected in the mature Daqu . Slightly increase in the content of alcohols was found in the enhanced group by fungal inoculation, including ethanol (46.58 ± 1.36 mg kg −1 ), isobutanol (0.19 ± 0.04 mg kg −1 ) and isoamyl alcohol (1.55 ± 0.13 mg kg −1 ). This study demonstrated that bioaugmentation had a positive effect on the amylase activity, main volatile compounds and microbial community richness. Abstract : Daqu production process and analysis.